Therapeutic modalities and postural balance of patients with knee osteoarthritis: systematic review - Andressa Silva; Marco Túlio de Mello; Sebastião Augusto Gávea Junior; Sandra Souza de Queiroz; Sergio Tufik; Stela Márcia Mattiello
AbstractObjective The objective of this review was to evaluate the evidence of the influence of therapeutic modalities on postural balance in patients with knee osteoarthritis (OA).Methods A search for published papers on therapeutic modalities was conducted using the Pubmed, Medline, Lilacs and SciELO databases. The keywords "knee" and "balance" in combination with "osteoarthritis" were used as the search strategy. Randomized controlled clinical trials published in the last 10 years in either English or Portuguese were selected. The PEDro scale was applied to assess the quality of the selected clinical trials.Results A total of 46 studies of patients with knee OA were found, of which seven were analyzed in full and 39 were excluded because they did not meet the inclusion criteria. Of the seven studies reviewed, six were considered to have a high methodological quality on the PEDro scale. Several therapeutic modalities were found (physical exercise, hydrotherapy, electrotherapy and manual therapy), and postural balance improved in only three studies.Conclusion The studies included in this systematic review had a high methodological quality, so it can be concluded that the therapeutic modalities used in those studies improved postural balance in patients with knee OA.